Nurse practitioner interactions in acute and long-term care: an exploration of the role of knotworking in supporting interprofessional collaboration. Issue 1 (December 2015) - Hurlock-Chorostecki, Christina; van Soeren, Mary; MacMillan, Kathleen; Sidani, Souraya; Donald, Faith; Reeves, Scott
Abstract Background Interprofessional care ensures high quality healthcare. Effective interprofessional collaboration is required to enable interprofessional care, although within the acute care  hospital setting interprofessional collaboration is considered suboptimal. The integration of nurse practitioner roles into the acute and long-term care settings is influencing enhanced care. What remains unknown is how the nurse practitioner role enacts interprofessional collaboration or enables interprofessional care to promote high quality care. The study aim was to understand how nurse practitioners employed in acute and long-term care settings enable interprofessional collaboration and care. Method Nurse practitioner interactions with other healthcare professionals were observed throughout the work day. These interactions were explored within the context of "knotworking" to create an understanding of their social practices and processes supporting interprofessional collaboration. Healthcare professionals who worked with nurse practitioners were invited to share their perceptions of valued role attributes and impacts. Results Twenty-four nurse practitioners employed at six hospitals participated. 384 hours of observation provided 1, 284 observed interactions for analysis. Two types of observed interactions are comparable to knotworking. Rapid interactions resemble the traditional knotworking described in earlier studies, while brief interactions are a new form of knotworking with enhanced qualities that more consistently result in interprofessional care. Nurse practitioners were the most common initiators of brief interactions. Conclusions Brief interactions reveal new qualities of knotworking with more consistent interprofessional care results. A general process used by nurse practitioners, where they practice a combination of both traditional (rapid) knotworking and brief knotworking to enable interprofessional care within acute and long-term care settings, is revealed.